A retrospective review of cryoprecipitate transfusion practice in Kuala Lumpur Hospital - Iliassa, Intan Iliana (Asian J Transfus Sci, 2016)
BACKGROUND: Cryoprecipitate is generally used to treat bleeding patients with hypofibrinogenemia, and the transfusion decision is guided based on published guidelines. AIM: This study aimed to evaluate the practice appropriateness in accordance to cryoprecipitate transfusion guidelines in Hospital Kuala Lumpur. METHODOLOGY: This cross-sectional study of 117 cryoprecipitates transfused adult patients was conducted in Kuala Lumpur Hospital from January to June 2012. The compliance of the indication of cryoprecipitate was considered as appropriate if indicated for patients who have hypofibrinogenemia (<1.0 g/L) with bleeding, or otherwise inappropriate if pretransfusion fibrinogen level was more than 1.0 g/L, pretransfusion fibrinogen level was not examined and posttransfusion fibrinogen level more than 1.5 g/L. RESULTS: Most of the cryoprecipitate prescriptions were found to be inappropriate, which read 81.2% (95% confidence interval = 0.740, 0.880). Patients who underwent neurovascular surgery were the major recipient of cryoprecipitate, but majority of the prescription was found not appropriate. The decision to transfuse cryoprecipitate was found mostly appropriate when was guided by fibrinogen (52.2%), but the percentage dropped to 10.6% when pretransfusion fibrinogen test was not performed. Regrettably, only 19.7% of total cryoprecipitate were given based on pretransfusion fibrinogen level.